Spatial distributions and homolog profiles of chlorinated nonane paraffins, and short and medium chain chlorinated paraffins in soils from Yunnan, China. (May 2020) - Wang, Kunran; Gao, Lirong; Zhu, Shuai; Cui, Lili; Qiao, Lin; Xu, Chi; Huang, Di; Zheng, Minghui
Abstract: To preliminarily investigate the occurrence, spatial distributions, homolog compositions, and ecological risks of chlorinated paraffins (CPs) in Yunnan, China, 110 soil samples were collected from an area part of Yunnan, representative of the whole Yunnan area, where had similar characteristics to most parts of Yunnan and 22 pooled soil samples were analyzed for 50 CP congener groups (C9 –17 Cl5–10 ). The chlorinated nonane paraffin (C9 -CP), short chain (SCCP), and medium chain chlorinated paraffin (MCCP) concentrations in soil samples were 8–109 ng/g (average 39 ng/g), 79–948 ng/g (average 348 ng/g), and 20–1206 ng/g (average 229 ng/g), respectively. The C9 -CP homologs contributed 5%–16% of the C9–13 -CP concentrations in soils. No significant correlation was found between CP concentrations and the total organic carbon content ( P > 0.05). The CP levels in soils from Yunnan were at a medium level compared with those in other areas worldwide. Human activity and atmosphere deposition would influence the levels and spatial distributions of CPs in this area. The concentrations of CPs in east area were higher than those in west area. C10 Cl6–7 were the major SCCP congeners and C14 Cl6–7 were the major MCCP congeners. Principal component analysis indicated that SCCPs and MCCPs came from different sources. A preliminary risk assessment indicated that these concentrations of CPs in soil from Yunnan do not pose a significant ecological risk for soil organisms. Graphical abstract: Image 1 Highlights: Chlorinated nonane paraffins (C9 -CPs) were analyzed in soils from Yunnan, China. Short and medium chain chlorinated paraffins (SCCPs and MCCPs) were detected. C10 Cl6–7 were the major SCCP congeners and C14 Cl6–7 were the major MCCP congeners. The spatial distributions were related to human activities and atmosphere deposition. The sources of SCCPs and MCCPs were different.